Exploring EFL Students’ Perceptions of ‘Perplexity’ AI Use and Abuse in Indonesia - Asmara, Yanti; Indrayadi, Toni; Reko Hary Putra (Universitas Muhammadiyah Surakarta, 2025)
This study investigates English Education students’ perceptions of the use and potential abuse of Perplexity, an AI-based platform, in completing academic assignments. Employing a quantitative survey design, the study used a self-administered questionnaire consisting of 12 items measured using a five-point Likert scale. Data were obtained from 34 students at an Islamic Institute in Jambi Province, Indonesia. The instrument was validated by experts and tested for reliability using KMO, Bartlett’s Test, EFA, and Cronbach’s Alpha. The results indicate that students exhibit a strong awareness of ethical and academic implications in using Perplexity AI. Most participants acknowledged that while the tool enhances learning efficiency, excessive reliance may hinder creativity, critical thinking, and academic honesty. Students perceived Perplexity as both beneficial and potentially problematic if misused. The study underscores the need for Islamic higher education institutions to develop comprehensive AI ethics guidelines, integrate digital literacy and moral instruction into curricula, and promote responsible, value-based AI use that aligns technological advancement with academic integrity.